Influence of metabolizable energy and protein levels on age and weight at puberty in male buffalo - MONDAL, GOUTAM; TALUKDAR, PAPORI; DAS, TAPAN KUMAR; BHAKAT, MUKESH; MOHINI, MADHU (The Indian Journal of Animal Sciences, 2021)
The objective of the present study was to determine the effects of different levels of metabolizable protein (MP) and metabolizable energy (ME) on nutrients utilization, growth performance, age and weight at puberty of Murrah male buffalo calves. Sixteen growing male buffalo calves weighing around 310Â±15 kg were divided into four groups of 4 animals each. The animals were offered four different total mixed rations containing different ME and MP levels, viz. 100,100; 115,100; 100,115; 115,115% as per ICAR (2013) standard in groups T1, T2, T3 and T4, respectively. The animals were fed individually ad lib. from around 13 months of age to age at puberty and at the 18 months a metabolic trial was conducted. Dry matter intake in calves fed all the treatment diets remained similar. Feed conversion ratio (FCR), crude protein conversion ratio (CPCR) and metabolisable energy conversion ratio (MECR), live weight gain were also similar among the groups. Nutrient intake, digestibility and N balance were similar in all the groups. Age at puberty was comparatively lower (around 20 months) in T4 than other groups (20â€“ 24 months), while body weight at that time was similar in all the groups. In conclusion, there were no significant improvement in body weight, ADG, nitrogen balance, age and weight at puberty in male buffalo calves with 15% increase in MP and ME in diet.